2023
DOI: 10.3390/d15050601
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effects of Habitat Change on Migratory Bird Movements and Avian Influenza Transmission in the East Asian-Australasian Flyway

Abstract: Wild waterbirds, and especially wild waterfowl, are considered to be a reservoir for avian influenza viruses, with transmission likely occurring at the agricultural-wildlife interface. In the past few decades, avian influenza has repeatedly emerged in China along the East Asian-Australasian Flyway (EAAF), where extensive habitat conversion has occurred. Rapid environmental changes in the EAAF, especially distributional changes in rice paddy agriculture, have the potential to affect both the movements of wild m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…It is noteworthy that intercontinental migration of wild and aquatic birds has been linked to virus dispersal and spillover to domestic avian species, including domestic chickens [63][64][65][66][67][68]. Previous studies have reported various flyways through which several avian species migrate to overwinter in different parts of the world [69][70][71][72][73]. Several hotspots for avian virus spillover occur in Africa on migratory bird flyways [74][75][76][77][78][79][80].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that intercontinental migration of wild and aquatic birds has been linked to virus dispersal and spillover to domestic avian species, including domestic chickens [63][64][65][66][67][68]. Previous studies have reported various flyways through which several avian species migrate to overwinter in different parts of the world [69][70][71][72][73]. Several hotspots for avian virus spillover occur in Africa on migratory bird flyways [74][75][76][77][78][79][80].…”
Section: Discussionmentioning
confidence: 99%